Neonatal-onset familial hemophagocytic lymphohistiocytosis: a case report with genetic confirmation of PRF1 mutations - Lyu, Xiaoyun; Wei, Pu; Zhu, Libo; Zhang, Wei (Frontiers in Genetics, 2025)
Familial hemophagocytic lymphohistiocytosis (FHL) is a rare, inherited immune-dysregulation syndrome that can present in the neonatal period and progress rapidly without timely recognition. We report a full-term female who developed abdominal distension, fever, hepatosplenomegaly, and coagulopathy within hours of birth, with multiorgan failure leading to death on day 5 despite intensive care and broad antimicrobial coverage. This timing, essentially at birth with death on day 5, is exceptionally rare in FHL2 and clinically instructive for sepsis-like neonatal presentations. Postmortem whole-exome sequencing identified compound heterozygous PRF1 variants, c.1131C>A (p.Cys377Ter) and c.65delC (p.Pro22Argfs*29), confirming FHL type 2. The presentation closely mimicked culture-negative neonatal sepsis, underscoring the diagnostic challenge of distinguishing primary HLH from infectious and metabolic conditions in early life. This case highlights the need for early clinical suspicion and rapid genomic testing in neonates with fulminant, sepsis-like inflammation. While HLH-directed therapy followed by hematopoietic stem-cell transplantation remains the standard pathway to improve survival, the fulminant neonatal course can outpace therapeutic windows, emphasizing the value of streamlined access to urgent genetics and specialist input.